Implementation of Problem Based Learning Models to Improve the Learning Outcomes of Class V Students at Natural Science Subject Matter - Gunarti, Ratna (Universitas Sebelas Maret, 2022)
The background of this research is due to the low learning outcomes in science mupel, the teacher only uses conventional methods or lectures in the learning process, causing students to be passive in the learning process so that learning outcomes are low. This study aims to improve the learning outcomes of fifth grade students in science learning, using the Problem Based Learning (PBL) learning model. The research being conducted was Classroom Action Research (CAR), research subjects of class V at SD Negeri 1 Potronayan, carried out in two cycles in September Semester 1 of the 2020/2021 Academic Year. In the first cycle of students who completed working on evaluation questions by 62%. In cycle II, students who finished working on evaluation questions were 85%. These results indicate that the application of the PBL learning model can improve students' critical thinking skills so that student learning outcomes can increase, especially in class V science lesson at SD Negeri 1 Potronayan.